Chemical methods to synthesize FeTiO3 powders - Mona, J.; Kale, Sangeeta N.; Gaikwad, A. B.; Murugan, A. Vadivel; Ravi, V. (Materials Letters, 2006)
Three different techniques were used to synthesize FeTiO3 powders. The first method is simple coprecipitation of both Fe and Ti ions under basic conditions using standard ammonia solution from aqueous ferric nitrate and titanium oxy chloride. This precipitate on heating at 400 degrees C produces ilmenite phase. The second method is to digest hydroxide precipitates at 100 degrees C to form FeTiO3 phase. The third technique is to make use of citrate process to form FeTiO3 powders. The phase contents and lattice parameters were Studied by powder X-ray diffraction (XRD). Particle size and morphology were studied by Transmission Electron Microscopy (TEM). (c) 2005 Elsevier B.V. All tights reserved.
Keywords: Chemical synthesis; Electron microscopy; electronic materials; X-ray methods

Co-precipitation technique for the preparation of ferroelectric BaBi2Ta2O9 - Dhage, S. R.; Pasricha, R.; Murugan, A. Vadivel; Ravi, V. (Materials Chemistry and Physics, 2006)
A simple co-precipitation technique had been successfully applied for the preparation of pure ultrafine single phase BaBi2Ta2O9 (BBT). Ammonium hydroxide and ammonium oxalate were used to precipitate Ba2+, Bi3+ and Ta5+ cations simultaneously. No pyrochlore phase was found while heating powder at 800 degrees C and pure BaBi2Ta2O9 phase was found to be formed by X-ray diffraction. Particle size and morphology was studied by transmission electron spectroscopy (TEM). The room temperature dielectric constant at 1 kHz is 350. The ferroelectric hysteresis loop parameters of these samples were also studied. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Chemical synthesis; electronic material; ferroelectricity; Oxides

Coprecipitation technique to prepare Sr0.5Ba0.5Nb2O6 - Murugan, A. Vadivel; Gaikwad, A. B.; Samuel, V.; Ravi, V. (Bulletin of Materials Science, 2006)
An aqueous mixture of ammonium oxalate and ammonium hydroxide was used to coprecipitate barium and strontium ions as oxalates and niobium ions as hydroxide under basic conditions. This precursor on calcining at 750 degrees C yielded Sr0.5Ba0.5Nb2O6 phase. This is a much lower temperature than that prepared by traditional solid state method (1000 degrees C) as reported for the formation of Sr0.5Ba0.5Nb2O6 (SBN). Transmission electron microscopic (TEM) investigations revealed that the average particle size was 80 nm for the calcined powders. The room temperature dielectric constant at I kHz was found to be 1100. The ferroelectric hysteresis loop parameters of these samples were also studied.
Keywords: Ceramics; Electron microscopy; ferroelectricity; Oxides; X-ray diffraction

Cyclic voltammetry, electrochemical impedance and ex situ X-ray diffraction studies of electrochemical insertion and deinsertion of lithium ion into nanostructured organic-inorganic poly(3,4-ethylenedioxythiophene) based hybrids - Murugan, A. Vadivel; Reddy, M. V.; Campet, Guy; Vijayamohanan, K. (Journal of Electroanalytical Chemistry, 2007)
In this work, we discuss the electrochemical insertion and deinsertion of lithium into poly(3,4-ethylenedioxythiophene) PEDOT-V(2)O(5) nanohybrids by using cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and powder ex situ X-ray diffraction (XRD) studies with special emphasis on their application potential as cathode materials for rechargeable Lithium batteries. The interlayer spacing of crystalline V(2)O(5) expands from 0.43 to 1.41 nm by the intercalation of PEDOT nanoribbons prepared by a microwave irradiation method. Cyclic voltammetry studies of PEDOT-V(2)O(5) hybrid at a slow scan rate of 0.058 mVs(-1) between 2.0-4.3 V vs. Li/ Li(+), demonstrates that structural transitions Of V(2)O(5) are suppressed and more facile intercalation features appear in terms of well-defined reversible cathodic and anodic peaks when compared to that at higher scan rate. Electrochemical Impedance studies of PEDOT-V(2)O(5) hybrid as cathode at ambient temperature with lithium metal foil as both counter and reference electrodes in 1 M LiPF(6) in a mixture of ethylene and diethylcarbonate (50:50 by volume) between the range 2.0-4.3 V reveals the usefulness of these materials. The observed capacity fading during cycling in terms of surface passivation and structural transformations is also investigated by CV, EIS and XRD analysis. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: cyclic voltammetry; ex situ XRD studies; high capacity lithium batteries; impedance studies; nanostructured hybrid materials